SCHOOL BASED MANAGEMENT (SBM) TO IMPROVE QUALITY OF EDUCATION IN KHM NUR JUNIOR HIGH SCHOOL SURABAYA - Suhroh, Ulfa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
AbstractCurrently, education management in Indonesia recognizes two mechanisms,namely centralization and decentralization system, in the centralized systemof education administration regulated by the central government. This studyaims to find out how the implementation of School Based Management(SBM) in KHM NUR Junior High School Surabaya, knowing what programsare implemented in KHM NUR Junior high School Surabaya and aims todetermine what factors that support and hinder the implementation of SchoolBased Management (SBM) in an effort to improve the quality of education atKHM NUR Junior High School Surabaya. The type of research used in thisstudy is Field Research, which is studying intensively about the background ofthe present state, in the interaction of a social, individual, group, institution,and society. Technique of data analysis used qualitative descriptive. Thefindings of this study can be concluded; first: Implementation of School BasedManagement (SBM) at KHM. NUR Junior High School Surabaya has beenwell scheduled. Second: The programs that have been implemented as theimplementation of School Based Management (SBM) in KHM. NUR JuniorHigh School Surabaya in academic and non-academic field. Third: Supportingand inhibiting factors in the implementation of School Based Management(SBM) in KHM. NUR Junior High School Surabaya among others comes fromthe intern and extern of the school.Â Keywords: School Based Management (SBM), Quality of Education.